2010
DOI: 10.1007/s11669-010-9791-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Description of the Ag-Pb-Te Ternary System

Abstract: Tellurium is an unwanted admixture in silver thus it is important to optimize tellurium removal from Ag by controlling its distribution between the liquid, slag and gaseous phases. Consequently, the knowledge of the state of thermodynamic equilibrium which determines the distribution of tellurium between these phases is very important. For its prediction it is necessary to know the thermodynamic description of every phase. In the present paper an attempt has been made to work out a thermodynamic description of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The thermodynamic models employed in this work are based on previous assessments by Gierlotka et al [12,31] on the Pb-Te system. In these expressions, the Gibbs energies G ϕ m of each phase ϕ taking part in the equilibria are defined using the models described below.…”
Section: Thermodynamic Models For the Calphad Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermodynamic models employed in this work are based on previous assessments by Gierlotka et al [12,31] on the Pb-Te system. In these expressions, the Gibbs energies G ϕ m of each phase ϕ taking part in the equilibria are defined using the models described below.…”
Section: Thermodynamic Models For the Calphad Methodsmentioning
confidence: 99%
“…Thus, following Ref. [31], in this work we have also used the associate model [36] to describe this phase. In CALPHAD terminology, the term "associate" is used to denote an association between unlike atoms when the attractive forces between the atoms are not strong enough to form a stable chemical molecule.…”
Section: Liquidmentioning
confidence: 99%
See 1 more Smart Citation
“… The integral mixing enthalpy of liquid Ag-Mg-Pb alloys at 1116 K, for the following intersections: (a)—Series A (Mg 0.25 Pb 0.75 ) 1−x Ag x —blue line: data calculated with Equation (4), blue diamonds—experimental data; (b)—Series B (Mg 0.50 Pb 0.50 ) 1−x Ag x —green line: data calculated with Equation (4), green circles—experimental data; (c)—Series C (Mg 0.75 Pb 0.25 ) 1−x Ag x —red line: data calculated with Equation (4), red rectangles—experimental data. The purple dash line is the integral molar mixing enthalpy of Ag–Mg [ 10 ] liquid alloys, and the brown dash-dot line is the integral molar mixing enthalpy of Ag–Pb [ 17 ] liquid alloys. …”
Section: Figurementioning
confidence: 99%
“…The Ag–Pb phase diagram is a simple eutectic system and has been widely investigated [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. A detailed review can be found in [ 16 ].…”
Section: Introductionmentioning
confidence: 99%